Strategi Penanganan Daerah Rawan Kecelakaan Di Ruas Jalan Kota Pekanbaru - Frans Tohom; Brasie Pradana Sela Bunga Riska Ayu (Borneo Engineering : Jurnal Teknik Sipil, 2022)
The increase in population and the number of motorized vehicles is a factor causing the increase in traffic accidents. In the city of Pekanbaru there is an increase in the number of residents by 2.3% each year and an increase in the number of motorized vehicles by 6.8%. Traffic accidents in Pekanbaru were recorded as many as 576 incidents in the 2018-2020 period with the death toll increasing every year, added up to 38, 40, and 53 people. For this reason, this study aims to identify accident-prone locations, analyze accident characteristics, and develop strategies for handling accident-prone locations in the city of Pekanbaru. Identification of accident-prone locations is carried out using the frequency, AEK, and UCL methods. Analysis of accident characteristics is carried out using the 5W+1H approach. The results of the study indicate that the accident-prone location is the Jl. Siak II, Sp. Palas-City Boundary, and Jl. Yos Sudarso. Analysis of accident characteristics shows that the dominant type of accident that occurs is due to lack of anticipation with the type of front-to-front collision, involving a motorcycle, and occurring during the day. This study recommends 3 recommendations, namely: Traffic Engineering, Education, and Law Enforcement.